InsIghts Into the mechanIsm of natural terpenoIds as NF-κB InhIBItors: an overvIew on theIr antIcancer potentIal - Jain, H.; Dhingra, N.; Narsinghani, T.; Sharma, R. (Experimental Oncology, 2016)
The transcription factor, nuclear factor kappa B (NF-kB) is one of the principal inducible protein in mammals known to control the gene expression in many critical physiological responses such as oxidative stress, inflammation etc. and has been shown to play an important role in the pathogenesis of cancer. Terpenoids are major constituents present in nutritionally used fruits, vegetables and different spices which possess various pharmacological action including anticancer activity. Various terpenoids, viz. monoterpenoids, sesquiterpenoids, diterpenoids, sesterterpenoids, triterpenoids, tetraterpenoids and polyterpenoids inhibit NF-kB signaling pathway through IkB phosphorylation, DNA binding, p65 translocation etc. Keeping in mind these facts, the present review revealed the anti-cancer potential of naturally occurring terpenoids highlighting their mechanism of NF-kB inhibition. This review also focuses on some of the naturally occurring terpenoids belonging to various chemical categories with potential inhibitory effects on NF-kB and their role in the treatment of cancer.